2014
DOI: 10.1063/1.4875457
|View full text |Cite
|
Sign up to set email alerts
|

Broad compositional tunability of indium tin oxide nanowires grown by the vapor-liquid-solid mechanism

Abstract: Indium tin oxide nanowires were grown by the reaction of In and Sn with O2 at 800 °C via the vapor-liquid-solid mechanism on 1 nm Au/Si(001). We obtain Sn doped In2O3 nanowires having a cubic bixbyite crystal structure by using In:Sn source weight ratios > 1:9 while below this we observe the emergence of tetragonal rutile SnO2 and suppression of In2O3 permitting compositional and structural tuning from SnO2 to In2O3 which is accompanied by a blue shift of the photoluminescence spectrum and increase in c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(44 citation statements)
references
References 19 publications
1
42
1
Order By: Relevance
“…We do not observe the fluorite structure of In x Sn y O 3.5 as shown recently by Meng et al [19] who observed a flux-induced crystal phase transition in the VLS growth of Sn-doped In 2 O 3 NWs. The PL of the Sn-doped In 2 O 3 NWs was found to be broad with a maximum at λ = 500 nm or 2.5 eV that shifts to 450 nm or ≈2.8 eV upon reducing the content of Sn to 1 % which also results into an increase in the carrier lifetime as shown previously by time-resolved PL [11]. The PL of the as-grown Sn-doped In 2 O 3 NWs at 2.8 eV, which is shown in Fig.…”
Section: Resultsmentioning
confidence: 50%
See 4 more Smart Citations
“…We do not observe the fluorite structure of In x Sn y O 3.5 as shown recently by Meng et al [19] who observed a flux-induced crystal phase transition in the VLS growth of Sn-doped In 2 O 3 NWs. The PL of the Sn-doped In 2 O 3 NWs was found to be broad with a maximum at λ = 500 nm or 2.5 eV that shifts to 450 nm or ≈2.8 eV upon reducing the content of Sn to 1 % which also results into an increase in the carrier lifetime as shown previously by time-resolved PL [11]. The PL of the as-grown Sn-doped In 2 O 3 NWs at 2.8 eV, which is shown in Fig.…”
Section: Resultsmentioning
confidence: 50%
“…1a while their lengths reached up to 100 μm. We have shown previously that the Sn-doped In 2 O 3 NWs have the cubic bixbyite crystal structure of In 2 O 3 as confirmed by GIXD but also by high resolution transmission electron microscopy (HRTEM) analysis which showed that the lattice spacing is equal to 0.718 nm and corresponds to the d-spacing of the {−1,1,0} crystallographic planes of the cubic bixbyite crystal structure of In 2 O 3 [11]. However, we also observed the formation of SnO 2 nanoparticles with a tetragonal rutile crystal structure on the surface of the Sn-doped In 2 O 3 NWs as shown by the inset of Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations